What Are We Comparing in Comparative Negligence? - Paul H. Edelman (Washington University Law Review, 2007)
This Article begins the formal study of how juries should calculate the percentages of negligence they are required to provide. Based on the standard model of negligence from law and economics, I will provide a specific framework for juries to use. This framework determines fault assessment based on different kinds of negligence torts. I distinguish among the methods of apportionment by examining the incentives they give for the parties to exercise care. As a consequence of this analysis, I make specific recommendations for jury instructions in comparative negligence cases. This Article proceeds in four parts. After a brief discussion in Section II of what juries are asked to do in assigning responsibility in comparative negligence cases, I will introduce three new concepts to analyze the nature of negligence cases. In Section III I classify two party negligence cases as being either commensurable or incommensurable, depending on whether the nature of the care to be taken by the two parties lies on the same or incomparable scales. Since a jury will be called upon to compare the levels of care taken and their ability to do so is radically different in the two cases, this distinction is an important one in comparative negligence regimes.
Keywords: Comparative law; Torts; Comparative negligence; Compensatory damages – Economic aspects